Extracurricular Basketball Shoot Lay-Up Ability Survey Of Students Of SMK Negeri 1 Bengkulu City - Fuji Pebrianto; Deffri Anggara; Dolly Apriansyah (Sinar Sport Journal, 2022)
This research is motivated by the game of basketball in schools, especially in high school, which is one of the game sports that is included in the curriculum as a compulsory sport to be taught. shoot on students of SMK Negeri 1 Bengkulu City. This type of research is qualitative research. The method used in this study is to use the lay up shoot technique. The subjects of this research were students of SMK Negeri 1 Bengkulu City. Data collection techniques are carried out in several ways, namely observation and documentation studies. The results showed that from the data from the lay-up shoot research conducted by students at SMK Negeri 1 Bengkulu City, there were 10 students in the very good category, 9 in the good category, 7 in the moderate category, 5 in the poor category, 0 in the very poor category. . The overall results obtained by all students of SMK Negeri 1 Bengkulu City were mostly in the Very Good category, 5 male students and 5 female students.